Combined Effect of High Hydrostatic Pressure and Lysine or Cystine Addition in Low-Grade Surimi Gelation with Low Salt Content - Cando, Deysi; Moreno Conde, Helena María; Borderías, A. Javier; Skåra, T (Food and Bioprocess Technology, 2016)
The aim of this study was to reduce the sodium chloride (NaCl) level in surimi-based products by adding lysine or cystine in combination with high hydrostatic pressure (HHP). For experiments, Alaska pollock surimi was used to prepare gels in a factorial design (3 × 3 × 2) using three additive levels (no additive, lysine, and cystine), three NaCl levels (0, 0.3, and 3 %), and two HHP levels (0 and 300 MPa/10 min/10 °C). After blending, the pastes, consisting of surimi, additives, and different levels of salt, were stuffed into casings, high pressure treated, and stored at 5 °C for 24 h (suwari gel). Subsequently, samples were heated at 90 °C for 30 min (kamaboko-type gel). To assess the degree of protein denaturation prior to gelation at 90 °C, suwari gels were analyzed by differential scanning calorimetry to determine myosin denaturation enthalpy. Kamaboko-type gels were characterized by lightness properties, water binding capacity, and mechanical properties (by puncture test). Results showed that the pressure treatment at 300 MPa and/or the addition of lysine or cystine (0 and 0.1 %) to low-sodium-chloride samples (0 and 0.3 %) resulted in gels with similar quality characteristics to those with the regular 3 % sodium chloride addition, most likely due to the protein unfolding induced by both HHP treatment and the additives used. Spanish Ministry of Economy and Competitiveness and the Spanish National Research Council (CSIC )under the project AGL2011-24693 Peer Reviewed